Characterization and winemaking application of a novel pectin-degrading enzyme complex from Aspergillus sojae ATCC 20235 - Fratebianchi de la Parra, Dante (2017)
A novel pectin-degrading enzyme complex produced by Aspergillus sojae ATCC 20235 (PC-AS) using lowcost substrates was characterised in terms of its enzyme activities relevant in winemaking. This novel PC-AS was applied at the maceration/fermentation stage during the elaboration of 'Tempranillo' red wines to study its effect on colour development and the phenolic and amino acid wine composition. PC-AS polygalacturonase activity was the major enzyme activity detected and quantified under winemaking conditions (pH 3.5, 20 °C) and proved being stable and active in the presence of sulfur dioxide. Xylanase activity, albeit in lesser amounts, was also present in PC-AS, and neither pectinesterase, which produces methanol, nor β-glucosidase, which is detrimental to wine colour, were detected in PC-AS. This pectin-degrading complex promoted a faster colour extraction since maximum colour intensity of the enzyme treated wines was reached earlier compared to their controls. After 6 months of storage under winery conditions, wines elaborated with PC-AS presented higher concentrations of caffeic acid, coumaric acid and aspartic acid (p ˂ 0.05), suggesting an improved extraction of grape cell components. In conclusion, the application of PCAS yielded results that showed that it can be used in red winemaking to shorten the maceration time needed to reach high CI values and to improve the extraction of some phenolics and other compounds that enhance the quality of the final product.